2014
DOI: 10.1159/000376595
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Factors and Coronary Artery Calcification

Abstract: The effective prevention of cardiovascular disease (CVD) remains a global health challenge. Adopting a combined primary (prevention of the first episode of coronary heart disease or stroke) and primordial (prevention of the causal risk factors of CVD) prevention strategy is the best approach to prevent CVD. Most importantly, the primordial prevention strategy should in the first place be to promote cardiovascular health across individual and population levels by improving the underlying causal risk factors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…1,2 Individuals with clusters of cardiovascular risk factors, such as the metabolic syndrome (MetS), are reported to have an increased progression of CAC over time. 3,4 CAC is also more prevalent in older age and in men. 5 Clinically, CAC adds predictive power to traditional risk factors, mainly in medium-high risk score patients 6 and is thought to be a marker of a more advanced stage of CAD compared with carotid intima media thickness.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Individuals with clusters of cardiovascular risk factors, such as the metabolic syndrome (MetS), are reported to have an increased progression of CAC over time. 3,4 CAC is also more prevalent in older age and in men. 5 Clinically, CAC adds predictive power to traditional risk factors, mainly in medium-high risk score patients 6 and is thought to be a marker of a more advanced stage of CAD compared with carotid intima media thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that high levels of cardiorespiratory fitness in young adults is associated with a lower risk of having calcification in the coronary arteries and prevents the development of early atherosclerotic vascular disease. 3 Physical inactivity and sedentary behavior leads to accumulation of excess adipose tissue and a state of chronic inflammation which is a major factor in the development of non-communicable diseases (NCD). Data from the Pakistan Demographic and Health Survey 2013 shows that approximately 15% of the youth bulge in Pakistan is between the ages of 18 and 25 years, comprising mostly of college and university students.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that high levels of cardiorespiratory fitness in young adults are associated with a lower risk of having calcification in the coronary arteries and prevent the development of early atherosclerotic vascular disease [24]. Physical inactivity and sedentary behaviour lead to accumulation of excess adipose tissue and a state of chronic inflammation which is a major factor in the development of non-communicable diseases.…”
Section: Discussionmentioning
confidence: 99%